Determination of antioxidant activity of Balabilvashunti decoction and its raw materials through different analytical methods - Madhushika, K.D.C.; Hapuarachch, S.D.; Suresh, T.S.; Perera, P.K.; Kodithuwakku, N.D.; Dahanayake, J.M.; Arawwawala, L.D.A.M. (My University, 2024)
Balabilvashunti (BBS) is an ayurvedic polyherbal formulation composed of three plant ingredients; rhizome of Zingiber officinale (ZO), whole plant of Sida alnifolia (SA), and root bark of Aegle marmelos (AM). BBS is mainly prescribed by ayurveda physicians for geriatric conditions including joint diseases, diabetes, nervous and gastrointestinal disorders...